Readiness And Self-Efficacy Of Health Study Program Students In Facing Digital Transformation In The Society 5.0 Era At Jakarta In 2024 - Harahap, Sarah Geltri; Nia, Nia; Veronica, Veronica; Ellynia, Ellynia; Yurrita Mailintina; Keysha Amelia Citra; Arum Nadya Octania; Azizah Az'zahra; Rabecca Christin Chandra; Aurelia, Aurelia (Sean Institute, 2024)
The Society 5.0 era is an advancement that will connect technology with prospective health workers. The digital transformation of health that is developing in Indonesia requires the readiness of health students and self-efficacy to face the digital transformation of health as a form of change in the Socity 5.0 era. This study aims to determine the readiness of students of the health and self-efficacy study program in facing the Society 5.0 Era. This study is a descriptive research with a crossectional study design using primary data on 361 students from all study programs in educational institutions in Jakarta. The results of this study show that students have intellectual skills, interpersonal skills, and communication, personal skills, organizational skills in the medium range, while career readiness is at a high level. Student Work Readiness has a relationship with students' Self-Efficacy with a p value of 0.001. Students must be able to develop themselves in order to be able to adapt to the rapid development of the technological era. The participation of educators, and other factors are needed to support and create prospective graduates who have good job readiness and good self-efficacy.